2012
DOI: 10.1002/jbmr.1758
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation: Simulation of the cost-effectiveness and cost-utility of universal prevention strategies against osteoporosis-related fractures

Abstract: A patient-level Markov decision model was used to simulate a virtual cohort of 500,000 women 40 years old and over, in relation to osteoporosis-related hip, clinical vertebral, and wrist bone fractures events. Sixteen different screening options of three main scenario groups were compared: (1) the status quo (no specific national prevention program); (2) a universal primary prevention program; and (3) a universal screening and treatment program based on the 10-year absolute risk of fracture. The outcomes measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Osteoporosis is characterized by decreased bone stiffness, as signified by low bone mineral density (BMD), vertebral or nonvertebral fragility fractures, and disruption of bone microarchitecture. It is a significant health problem afflicting the global people [5, 6], and the female cases were more than male ones (5:2) older than 50 years of age, which brings about a disease burden of around £ 1.8 billion in the UK and £ 30 billion in whole Europe [7]. Although the high incidence rate of osteoporosis and osteoporotic fractures in the schizophrenic patients was first reported about 20 years ago [810], related reports about the increased risk of osteoporotic fracture and earlier onset of osteoporosis in the schizophrenic patients are seldom published [11].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is characterized by decreased bone stiffness, as signified by low bone mineral density (BMD), vertebral or nonvertebral fragility fractures, and disruption of bone microarchitecture. It is a significant health problem afflicting the global people [5, 6], and the female cases were more than male ones (5:2) older than 50 years of age, which brings about a disease burden of around £ 1.8 billion in the UK and £ 30 billion in whole Europe [7]. Although the high incidence rate of osteoporosis and osteoporotic fractures in the schizophrenic patients was first reported about 20 years ago [810], related reports about the increased risk of osteoporotic fracture and earlier onset of osteoporosis in the schizophrenic patients are seldom published [11].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Osteoporosis-related fractures are usually associated with increased morbidity and mortality, and increased healthcare costs. [5][6][7] Several therapies (including teriparatide, calcitonin, alendronate and strontium ranelate) have been shown to be well tolerated and effective in the prevention of osteoporosis. [8][9][10] Clinical studies have indicated that nitrogen-containing bisphosphonates not only inhibit bone resorption but also preserve bone mass, thereby reducing the risk of osteoporotic fractures.…”
Section: Introductionmentioning
confidence: 99%
“…From both the health economics and the clinical viewpoint, it is appropriate that treatment decisions on osteoporosis are based on the absolute risk of fracture as opposed to the consideration of relative risks and the impact of individual risk factors [3,[37][38][39]. Only with absolute risks of fracture and the quantified consideration of the effectiveness of interventions can the practicing clinician estimate the true value of an intervention and, thus, its indication.…”
Section: Discussionmentioning
confidence: 99%